CONTRIBUTION TO THE KNOWLEDGE OF PHYLLONORYCTER ISSIKII (KUMATA, 1963) (LEPIDOPTERA, GRACILLARIIDAE) IN SERBIA (Acta Entomologica Serbica, 2018)
Phyllonorycter issikii (Kumata, 1963) is an invasive leaf-mining moth originating from Asia. It develops on plants from the genus Tilia. The first finding of this species in Serbia was in 2013, and since then, the range of the species has spread, and we have found it at five more localities on T. cordata and T. tomentosa. Ph. issikii was studied at two of these localities. The existence of two overlapping generations was determined. No significant differences in the intensity of the attack between them were noticed. Differences existed only between the localities where the research was conducted and between the Tilia species on which Ph. issikii was found. As regards the lime species, the moth preferred T. cordata to T. tomentosa at both localities. Two species of parasitoids were reared from the collected material: Pediobius saulius (Walker, 1839) and Minotetrastichus frontalis (Nees, 1834).